Treatment outcomes of childhood PICALM::MLLT10 acute leukaemias - Mark, Catherine; Meshinchi, Soheil; Joyce, Brooklyn; Gibson, Brenda; Harrison, Christine; Bergmann, Anke K; Goemans, Bianca F; Pronk, Cornelis Jan H; Lapillonne, Helene; Leverger, Guy; Antoniou, Evangelia; Schneider, Markus; et al. (British journal of haematology, 2024)
The prognostic impact of PICALM::MLLT10 status in childhood leukaemia is not well described. Ten International Berlin Frankfurt Münster-affiliated study groups and the Children's Oncology Group collaborated in this multicentre retrospective study. The presence of the PICALM::MLLT10 fusion gene was confirmed by fluorescence in situ hybridization and/or RNA sequencing at participating sites. Ninety-eight children met the study criteria. T-cell acute lymphoblastic leukaemia (T-ALL) and acute myeloid leukaemia (AML) predominated 55 (56%) and 39 (40%) patients, respectively. Most patients received a chemotherapy regimen per their disease phenotype: 58% received an ALL regimen, 40% an AML regimen and 1% a hybrid regimen. Outcomes for children with PICALM::MLLT10 ALL were reasonable: 5-year event-free survival (EFS) 67% and 5-year overall survival (OS) 76%, but children with PICALM::MLLT10 AML had poor outcomes: 5-year EFS 22% and 5-year OS 26%. Haematopoietic stem cell transplant (HSCT) did not result in a significant improvement in outcomes for PICALM::MLLT10 AML: 5-year EFS 20% for those who received HSCT versus 23% for those who did not (p = 0.6) and 5-year OS 37% versus 36% (p = 0.7). In summary, this study confirms that PICALM::MLLT10 AML is associated with a dismal prognosis and patients cannot be salvaged with HSCT; exploration of novel therapeutic options is warranted.
Keywords: paediatric; Acute Disease; monomerní proteiny vytvářející klathrin; dítě; lymphoid neoplasia; transkripční faktory; výsledek terapie; fúzní onkogenní proteiny; lidé; Monomeric Clathrin Assembly Proteins; Transcription Factors; myeloid neoplasia; Oncogene Proteins, Fusion; Treatment Outcome; prognóza; retrospektivní studie; akutní myeloidní leukemie; Prognosis; akutní nemoc; hybridizace in situ fluorescenční; Child; In Situ Hybridization, Fluorescence; Retrospective Studies; Leukemia, Myeloid, Acute; Humans